The Middle East and the Malay World Contemporary Issues and Future Challenges - Alami, Abdolreza; Bilgrami, Muna H. (Gerakbudaya Enterprise, 2023)
The strong links between the Malay world and the Middle East have been shaped by interweaving forces, foremost among them the historical role of the spread of Islam, the modern colonizing forces of Europe, and more latterly the contemporary interests of World Powers. To bring focus to these relationships, a Two-day International Conference on 'The Middle East and Malay World: Contemporary Issues and Future Challenges' was jointly held in Kuala Lumpur in October 2022 by AsiaWE, AMEC, Bait Al Amanah, Academy of Malay Studies, University Malaya, with an emphasis on History, Politics, Culture, and Finance. Contributions centred around three areas: relations of the Muslim Malay Archipelago with the Middle East, the influence of the World Powers of the United States and China, and the position of Malaysia and Indonesia on Palestine. The chapters collected in this volume reveal to us these often hidden, historical landscapes of regional connections, reflecting ground level intermarriages of a vibrant trade and knowledge culture, the legacies of colonialism, and giving attention to the shifting axes of power in the 21st century. Tensions generated by intersecting forces of competing interests within these relationships are nowhere more visible than in the matter of Palestine. Several of these chapters highlight the opportunities that await judicious and wise working partnerships between the two regions.